(untitled) (Perner’s Contacts, 2009)
The article describes approache processes according to the apparats used in air traffic. General characteristics of separate approaches, introduction to document L8168 and analysis of one of the approaches according to apparats - circling approach are included in the artricle. Conclusion of the article focuses on air navigation development in following years.